Meningkatkan Kemampuan Mengenal Angka 1-20 Melalui Media Kincir Bilangan pada Disabilitas Rungu Berat - Tiara, Tiara Octarifka; Zulmiyetri, Zulmiyetri; Damri, Damri; Tsaputra, Antoni (Indo-MathEdu Intellectuals Journal, 2025)
Severely hearing-impaired children in the third grade of SLB Negeri 1 Lubuk Sikaping, the teacher tends to use lecture and question-and-answer methods, causing the children to easily get bored and have difficulty understanding number concepts. This study aims to improve the ability to recognize numbers through the number wheel media. The subjects are two severely hearing-impaired children. This study uses a classroom action research design with qualitative and quantitative approaches. The research subjects are two severely hearing-impaired children, namely GT and MR. Data collection was conducted through observation and analyzed descriptively. The analysis results show that there was a significant improvement: students' initial ability (GT 26%, MR 18%), at the end of cycle I (GT 63%, MR 56%), and at the end of cycle II (GT 100%, MR 88%). Thus, the use of the number wheel media is proven effective in improving the ability to recognize numbers 1-20 in children with severe hearing impairment.